Developing Shorf (Morphology) Instruction According to Rusydi Ahmad Thu‘Aimah, Mahmud Kamil An-Naqah, and Robert Lado - Fikri Amiq Setiawan; Muhbib Abdul Wahab; Akmal Walad Ahkas (RADJA PUBLIKA, 2026)
This study examines the development of Shorf (morphology) instruction through the perspectives of three prominent scholars: Rusydi Ahmad Thu‘aimah, Mahmud Kamil An-Naqah, and Robert Lado. The study is grounded in the significance of Arabic morphology as a foundational component for mastering structure and meaning in modern Arabic. Using a descriptive qualitative approach and library research, this study analyzes the key works of the three scholars. The findings indicate that Rusydi Ahmad Thu‘aimah emphasizes contextual and communicative approaches in teaching morphology; Mahmud Kamil An-Naqah highlights the integration of form, meaning, and language skills; while Robert Lado underscores the role of contrastive analysis in understanding cross-linguistic morphological differences. The synthesis of these perspectives leads to a functional, meaningful, and context-based model of Shorf instruction that integrates cognitive, affective, and communicative dimensions, thereby strengthening learners’ understanding of word structure and semantic function in Arabic language learning.